2020
DOI: 10.3389/fenvs.2020.00081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fungicide and Herbicide Chemical Exposure on Apis and Non-Apis Bees in Agricultural Landscape

Abstract: Fungicide and herbicide chemistries are commonly applied in agricultural production systems and other agricultural landscapes during flowering periods, which are concurrent with the timing of bee-dependent pollination services in many plant species. As a result, bees can be exposed to these pesticides while foraging crops and other flowering plants in the landscape where they have been administered. Laboratory and semi-field studies simulating these pesticide exposure scenarios have demonstrated lethal and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 72 publications
0
43
0
Order By: Relevance
“…This undoubtedly depicts a major knowledge gap, in particular, when considering that solitary bees of the genus Osmia are among the most pronounced generalist species [ 35 ], and are of high economic and commercial value for orchard pollination around the world [ 41 ]. While only a few studies have investigated the effects of combined pesticide exposure for solitary bee species (i.e., insecticide and fungicides), all indicating significant lethal or sublethal effects [ 28 , 33 , 42 ], similar effects of an insecticide in combination with a herbicide remain to be tested [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…This undoubtedly depicts a major knowledge gap, in particular, when considering that solitary bees of the genus Osmia are among the most pronounced generalist species [ 35 ], and are of high economic and commercial value for orchard pollination around the world [ 41 ]. While only a few studies have investigated the effects of combined pesticide exposure for solitary bee species (i.e., insecticide and fungicides), all indicating significant lethal or sublethal effects [ 28 , 33 , 42 ], similar effects of an insecticide in combination with a herbicide remain to be tested [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…38 While the intention of herbicide-based weed management in this context is to reduce the exposure of pollinators to toxic substances, there is the possibility that by using herbicide for management of groundcover, pollinators may be exposed to additional toxins. While less well researched than the impacts of insecticides, a number of studies over the last decade have shown that commonly used herbicides can have a range of negative impacts on bees, 39 with soil-nesting bees likely to be particularly vulnerable to exposure to herbicides applied to groundcover vegetation. 40 Kammerer et al 41 reported that soil-nesting bees made up the majority of apple-visiting bee species in a group of orchards near our study site (in south central Pennsylvania), though as with our observations, soil-nesting species were present in lower numbers and thus made only a small contribution to overall visitation.…”
Section: Discussionmentioning
confidence: 99%
“…Development from egg to adult differs among species, taking a relatively long time in bumblebees. On average, development in bumblebee males takes 24-28 days [6], while development takes approximately 24 days in male honeybees [1,7]. Several factors, such as the overall colony condition, temperature (brood nest), number of workers, and quality and availability of food resources (nutrients), have a crucial influence on the development time and quality of the male bumblebees produced [2].…”
Section: Life and Role Of Male Bees In Coloniesmentioning
confidence: 99%
“…After emergence, males gradually mature to copulate and transmit sperm to the spermathecae of queens. Estimates of sexual maturation range between 6-20 days after emergence in bumblebees [6] and 6-16 days in honeybees [7]. Efficient copulation and sperm viability are closely related to male quality characteristics such as birth weight, age, body size, and environmental conditions.…”
Section: Life and Role Of Male Bees In Coloniesmentioning
confidence: 99%
See 1 more Smart Citation